Biases in the measurement of labour market dynamics - Ronald Bachmann; Sandra Schaffner (Technische Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2009)
This paper analyses worker transitions on the German labour market derived from different data sources. These include the two German micro data sets which provide high-frequency observations on workers' employment and unemployment histories: the German Socioeconomic Panel (SOEP) and the IAB Employment Subsample (IABS). This exercise thus yields a comprehensive overview of German labour market dynamics. Furthermore, it highlights the differences between the results obtained from a retrospective survey, the SOEP, and a process-induced administrative data set, the IABS. In particular, our analysis shows which groups of the labour market are particularly affected by measurement error. We also show which role measurement issues play when establishing the stylised facts about the cyclicality of labour market dynamics.
Keywords: J63; J64; J62; 519; gross worker flows; SOEP; IABS; Arbeitsmobilität; Arbeitsmarktstatistik; Statistischer Fehler; Bias; Konjunkturelle Arbeitslosigkeit; Deutschland